2013
DOI: 10.1371/journal.pone.0071334
|View full text |Cite
|
Sign up to set email alerts
|

Expansion of Multipotent Stem Cells from the Adult Human Brain

Abstract: The discovery of stem cells in the adult human brain has revealed new possible scenarios for treatment of the sick or injured brain. Both clinical use of and preclinical research on human adult neural stem cells have, however, been seriously hampered by the fact that it has been impossible to passage these cells more than a very few times and with little expansion of cell numbers. Having explored a number of alternative culturing conditions we here present an efficient method for the establishment and propagat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
53
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(58 citation statements)
references
References 68 publications
5
53
0
Order By: Relevance
“…Comparison of transcriptome data and available data sets confirmed that all 3 types of somatic cells expressed a set of cell type specific markers. The n5-derived fibroblasts closely resembled MRC5 (human lung fibroblasts), BJ1 (human foreskin fibroblasts) and human skin fibroblasts; 20,21 the n5-derived neurons corresponded to the human gray and white matter brain cells; 22 and the transcriptome of our RPE cells was similar to previously published hRPE cells. 23,24,25 (for details see Supplemental Experimental Procedures Fig.…”
Section: Establishment Of the Hesm01-oskmn-dox Isogenic Systemsupporting
confidence: 66%
“…Comparison of transcriptome data and available data sets confirmed that all 3 types of somatic cells expressed a set of cell type specific markers. The n5-derived fibroblasts closely resembled MRC5 (human lung fibroblasts), BJ1 (human foreskin fibroblasts) and human skin fibroblasts; 20,21 the n5-derived neurons corresponded to the human gray and white matter brain cells; 22 and the transcriptome of our RPE cells was similar to previously published hRPE cells. 23,24,25 (for details see Supplemental Experimental Procedures Fig.…”
Section: Establishment Of the Hesm01-oskmn-dox Isogenic Systemsupporting
confidence: 66%
“…However, to our knowledge, the presence of a SOX2 + (SRY-like homeobox 2) glial progenitor subpopulation, which precedes the expression of these markers during the differentiation process to glial cells, has not been reported, although some preliminary studies claim the possibility of isolating SOX2 + cells from human white matter, among other brain regions [10]. This transcription factor plays critical roles throughout development and is required for the reprogramming of somatic cells in induced pluripotent cells (iPS) [11], [12].…”
Section: Introductionmentioning
confidence: 95%
“…A recent study has found that the generation and migration of new neurons is very much limited to the early childhood (Curtis et al, 2012). Less well-characterized in the human brain are proliferating NPCs in the hippocampus, white matter, and other regions, where cells isolated from the adult human brain are capable of generating both neurons and glia under culture conditions (Kukekov et al, 1999;Murrell et al, 2013;Nunes et al, 2003).…”
Section: Neurogenesis In the Human Brainmentioning
confidence: 99%